Estudo das propriedades fisico-químicas e tribológicas de condicionadores de metais e suas misturas com óleos lubrificantes para motor - Palma Calabokis, Oriana (2024)
Metal conditioners are marketed as products that enhance the efficiency of internal combustion engines by increasing power, reducing fuel consumption, and controlling the friction and wear of moving parts. However, there is a lack of detailed knowledge regarding their chemical composition, properties, and operational mechanisms, as scientific research validating their effects is limited. In response to this gap, this thesis studied the physicochemical and tribological properties of metal conditioners and their mixtures with engine lubricating oils in both laboratory and field tests. The work was presented in the form of a collection of three articles published in scientific journals. The publications focus on evaluating the effects of these aftermarket additives on the performance of small-capacity motorcycles, their physicochemical and tribological properties, and their corrosiveness to bronze alloy. The first article, rooted in field study, demonstrated under real-world operational conditions that metal conditioners afford protection to steel and aluminum alloy components of low-displacement motorcycles. This protection became apparent during the initial 7,000 km of engine running-in, even though components containing copper exhibited higher wear rates, still, these rates remained within acceptable predefined thresholds. Notably, the introduction of the conditioner did not compromise the properties or degradation pathways of the lubricants in use. The second publication demonstrated that adding a conditioner to an engine oil did not change the commercial oil’s physicochemical properties, showing a substantial anti-wear action (33%) at 80 °C. The third and final article addressed concerns regarding the corrosiveness of some metal conditioners towards copper alloys. It was found that when these conditioners are blended with engine oil, their corrosive potential is significantly reduced, leaving only the mild corrosive impact inherent to the additives already present in the engine oil. The comprehensive study provides a critical and scientifically grounded look at metal conditioners. It not only confirms their potential to improve the performance and durability of internal combustion engines but also emphasizes the importance of a deeper understanding of their composition, action mechanisms, and interactions with different materials.